Evaluation of Hospitalizations Preventable with Idealized Outpatient Care and Continuity of Care. Issue 3 (May 2021) - Li, Shawn X.; del Carmen, Marcela G.; Thompson, Ryan W.; Cafiero-Fonseca, Elizabeth T.; Rockett, Helaine; Ferris, Timothy G.; Terry, Dellara F.; Warner, Ana Sofia; Yu, Amy; Wasfy, Jason H.
ABSTRACT: Background: Unnecessary hospitalizations may pose the risk of iatrogenic complications, suboptimal patient experience, and increased cost. Administrative data lack granularity to understand the proportion and causes of hospitalizations preventable through optimizing care continuum (HPOCC). We aim to identify the incidence and causes of HPOCC through clinician-adjudicated chart review. Methods: A retrospective review was performed for inpatient admissions from the emergency department (ED) over 1 week. Each admission was reviewed by a clinician to determine whether it is an HPOCC defined as not requiring inpatient care with the assumption of idealized outpatient care and social support. Results: Of the 515 patients admitted from the ED, 31 (6.0%) patients were judged to have had an HPOCC. Causes of HPOCC include urgent diagnostics (9, 29.0%), unnecessary transfer from a long-term facility (7, 23.0%), needing IV therapy (5, 16.0%), benign incidental finding (5, 16.0%), diagnostic uncertainty in complex chronic illness (3, 10.0%), and lack of access to care for disposition (2, 6.0%). Conclusion: Hospitalizations preventable through optimizing care continuum account for about 1 in every 15 hospitalizations in an urban academic medical center. The need for urgent diagnostics accounts for a plurality of HPOCC and could be an important target for quality improvement.